Le Commerce de Céramiques Fines à Ammaia, une Ville du Sud de la Lusitanie (50 - 550 Apr. J. -C. ) - Quaresma, José Carlos (Roman and Late Antique Mediterranean Pottery Ser., 2021)
This volume presents the entire assemblage of fine wares (terra sigillata, lamps and thin-walled wares) from Ammaia, a Roman and Late Antique town located in the hinterland of southern Lusitania (presently in Portuguese territory).